Assessing Language Learning Outcomes through Digital Humanities - J M Kanthi Thilaka; C. Neelima (Digital Crossroads: Integrating Humanities, Science and Technology Edition 1, 2025)
Language learning is a cornerstone of human interaction, enabling cross-cultural communication and fostering global understanding. This paper explores how DH tools and methodologies enhance the assessment of language acquisition, focusing on linguistic skills, cultural competence, and learner engagement. Digital Humanities encompasses a range of tools and methods, such as text analysis, data visualization, corpus linguistics, and digital storytelling. Digital tools increase motivation and involvement by making the evaluation process more dynamic, interesting, and pleasurable for students. For instance, students feel more engaged in the learning process when they use collaborative platforms or annotation tools. By fostering interdisciplinary collaboration, educators and technologists can unlock the full potential of DH, creating transformative language learning experiences that prepare learners for a globalized world.